Photobiomodulation therapy for persistent neurosensory disorders after orthognathic surgery: a case report - Araújo, Rodrigo Ricco Teixeira Barbosa de; Santos, Alanna Maria Castro dos; Silvestre, Giovanna Gabrieli; Dantas, Elaine Maria Guará Lôbo (Brazilian Dental Science, 2026)
Objective: Orthognathic surgery is widely used to correct dentofacial deformities, but it can lead to postoperative neurosensory complications, such as paresthesia, which can significantly affect quality of life. This case report evaluates photobiomodulation therapy (PBMT) as a non-invasive intervention for persistent inferior alveolar nerve paresthesia refractory to conventional therapies. Case report: A 26-year-old woman with chronic neurosensory disorder after orthognathic surgery underwent PBMT with an 808 nm diode laser (Therapy XT, DMC®, continuous mode, in contact), spot area of 0.098 cm2, power of 100 mW and energy density of 1.02 W/cm2. The protocol consisted of ten consecutive sessions, performed with a seven-day interval between each application. Irradiation included 34 extraoral and 10 intraoral points, spaced 1 cm apart. The progressive dosimetry protocol was used: 2 J per point (initial 4 sessions) and 4 J per point (subsequent sessions), totaling 10 sessions. The reduced initial values of 30-60 (chin) and 10 (lower lip) evolved to 80-90 on the progressive sensitivity scale in the previously compromised areas, with no reports of adverse effects. Conclusion: This case report suggests the potential effectiveness of PBMT as a treatment for long-standing postoperative paresthesia; however, the findings are preliminary and cannot be generalized to all patients. Further controlled clinical studies are needed to confirm efficacy and support protocol standardization. KEYWORDS Case report; Low-level light therapy; Mandibular nerve; Orthognathic surgery; Paresthesia.